The Mitochondrial Connection: The Nek Kinases’ New Functional Axis in Mitochondrial Homeostasis - Fernanda L. Basei; Ivan Rosa e Silva; Pedro R. Firmino Dias; Camila C. Ferezin; Andressa Peres de Oliveira; Luidy K. Issayama; Livia A. R. Moura; Fernando Riback da Silva; Jörg Kobarg (Cells, 2024)
Mitochondria provide energy for all cellular processes, including reactions associated with cell cycle progression, DNA damage repair, and cilia formation. Moreover, mitochondria participate in cell fate decisions between death and survival. Nek family members have already been implicated in DNA damage response, cilia formation, cell death, and cell cycle control. Here, we discuss the role of several Nek family members, namely Nek1, Nek4, Nek5, Nek6, and Nek10, which are not exclusively dedicated to cell cycle-related functions, in controlling mitochondrial functions. Specifically, we review the function of these Neks in mitochondrial respiration and dynamics, mtDNA maintenance, stress response, and cell death. Finally, we discuss the interplay of other cell cycle kinases in mitochondrial function and vice versa. Nek1, Nek5, and Nek6 are connected to the stress response, including ROS control, mtDNA repair, autophagy, and apoptosis. Nek4, in turn, seems to be related to mitochondrial dynamics, while Nek10 is involved with mitochondrial metabolism. Here, we propose that the participation of Neks in mitochondrial roles is a new functional axis for the Nek family.